2014
DOI: 10.1094/pdis-02-14-0151-re
|View full text |Cite
|
Sign up to set email alerts
|

Lineage, Temperature, and Host Species have Interacting Effects on Lesion Development in Phytophthora ramorum

Abstract: Eyre, C. A., Hayden, K. J., Kozanitas, M., Griinwald, N. J., and Garbelotto, M. 2014. Lineage, temperature, and host species have interacting effects on lesion development in Phytophthora ramorum. Plant Dis. 98:1717-1727.There are four recognized clonal lineages of the pathogen Phy tophthora ramorum. The two major lineages present in North America are NA1 and NA2. With a few exceptions, NA1 is found in natural forest ecosystems and nurseries, and NA2 is generally restricted to nurseries. Isolates from the NA1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 67 publications
2
16
0
Order By: Relevance
“…Although infection on bay laurel leaves can rebound quickly following drought conditions (Eyre et al. ), our results suggest that this may not necessarily increase pathogen spillover, because we also found that disease prevalence was greater when temperatures are consistently warm and wet. A generally warming climate would likely mean warmer temperatures year‐round, potentially increasing the success of pathogen spillover during the wet season, but also increasing heat exposure and reducing the pathogen load during the dry season.…”
Section: Discussionmentioning
confidence: 46%
“…Although infection on bay laurel leaves can rebound quickly following drought conditions (Eyre et al. ), our results suggest that this may not necessarily increase pathogen spillover, because we also found that disease prevalence was greater when temperatures are consistently warm and wet. A generally warming climate would likely mean warmer temperatures year‐round, potentially increasing the success of pathogen spillover during the wet season, but also increasing heat exposure and reducing the pathogen load during the dry season.…”
Section: Discussionmentioning
confidence: 46%
“…On the contrary, in substrates with nil or negligible epidemiological role, either a high turnover of genotypes occurs (e.g., in water and soil), or genetic structural variations causing a significant change in phenotype can be observed (e.g., in oaks; Eyre et al. , ). Moreover, no genetic structure has been recorded when comparing populations from oaks and those from bays (Kasuga et al.…”
Section: Discussionmentioning
confidence: 99%
“…Zoospores were produced and counted as described in Eyre et al. (). Inoculations were performed as follows.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all trials, the severity of symptoms was significantly different between treatments and controls, further indicating that the length of the experiments was sufficient to draw conclusions, and saved us the unnecessary use of resources associated with longer trials. Additionally, it should be pointed out that other researchers have routinely performed experiments of comparable length to assess the virulence of Phytophthora species (Eyre, Hayden, Kozanitas, Grünwald, & Garbelotto, ) including P. cactorum (Lilja, Karjalainen, Parikka, Kammiovirta, & Nuorteva, ) and P. tentaculata (Meng & Wang, ; Rooney‐Latham & Blomquist, ). Although mortality (a qualitative variable) can be assessed using longer experiments, quantitative variables including canker size and severity of canopy symptoms are often biased in longer trials, because the size of lesions and the appearance of the canopy cannot be considered reliable when plants are dead.…”
Section: Discussionmentioning
confidence: 99%